Inhibiting YAP in Endothelial Cells From Entering the Nucleus Attenuates Blood-Brain Barrier Damage During Ischemia-Reperfusion Injury - Gong, Shuaishuai; Ma, Huifen; Zheng, Fan; Huang, Juan; Zhang, Yuanyuan; Yu, Boyang; Li, Fang; Kou, Junping (Frontiers in Pharmacology, 2021)
The breakdown of the blood-brain barrier (BBB) aggravates brain damage in ischemic stroke. Endothelial detachment contributes to BBB disruption and neurovascular dysfunction, but its regulation in stroke has yet to be clarified. We investigated the function of Yes-associated protein 1 (YAP) in the endothelium on BBB breakdown during cerebral ischemia/reperfusion (I/R) injury. The effects of YAP on BBB dysfunction were explored in middle cerebral artery occlusion/reperfusion (MCAO/R)-injury model mice and using brain microvascular endothelial cells (BMEC) exposed to oxygen-glucose deprivation/reoxygenation (OGD/R) injury. The degree of brain injury was estimated using staining (2,3,5-Triphenyltetrazolium chloride, hematoxylin and eosin) and the detection of cerebral blood flow. BBB breakdown was investigated by examining the leakage of Evans Blue dye and evaluating the expression of tight junction (TJ)-associated proteins and matrix metallopeptidase (MMP) 2 and 9. YAP expression was up-regulated in the nucleus of BMEC after cerebral I/R injury. Verteporfin (YAP inhibitor) down-regulated YAP expression in the nucleus and improved BBB hyperpermeability and TJ integrity disruption stimulated by cerebral I/R. YAP-targeted small interfering RNA (siRNA) exerted the same effects in BMEC cells exposed to OGD/R injury. Our findings provide new insights into the contributions made by YAP to the maintenance of BBB integrity and highlight the potential for YAP to serve as a therapeutic target to modulate BBB integrity following ischemic stroke and related cerebrovascular diseases.